Yadnya Adalah Ketulusan, Bukan Kontestasi Yang Dibalut Gengsi Dalam Kehidupan Beragama - Damiyani, Ni Putu (Jayapangus Press, 2021)
In Hinduism, yadnya is something that is mandatory to do. Because humans were created by Ida Sang Hyang Widhi Wasa on the basis of yadnya. So that humans should maintain and develop themselves with yadnya as their guideline to improve and devote themselves to Ida Sang Hyang Widhi Wasa. Actually yadnya is a sincerity in life, yadnya comes from the Sanskrit word